Pollution status of polycyclic aromatic hydrocarbons in surface sediments from the Yangtze River Estuary and its adjacent coastal zone. (November 2016) - Wang, Chenglong; Zou, Xinqing; Gao, Jianhua; Zhao, Yifei; Yu, Wenwen; Li, Yali; Song, Qiaochu
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are mainly produced by incomplete combustion and are used as indicators of anthropogenic activities on the environment. This study analyses the PAHs level in the Yangtze River Estuary (YRE), an important component of Yangtze River and a developed and populated region in China. Surface sediments were collected from 77 sites at the YRE and its adjacent coastal zone (IACZ) for a comprehensive study of PAHs. Kriging interpolation technology and Positive matrix factorization (PMF) model were applied to explore the spatial distribution and sources of PAHs. Concentrations of 16 PAHs (ΣPAHs) varied from 27.2 ng g −1 to 621.6 ng g −1 dry weight, with an average value of 158.2 ng g −1 . Spatially, ΣPAHs exhibited wide fluctuation and exhibited an increasing tendency from north to south. In addition, ΣPAHs exhibited a decreasing trend with increasing distance between the estuary and IACZ. The deposition flux of PAHs indicated that more than 107.8 t a −1 PAHs was deposited in the study area annually. The results of the PMF model revealed that anthropogenic activities were the main sources of PAHs in the study area. Vehicle emissions and marine engines were the most important sources and accounted for 40.9% of the pollution. Coal combustion, petrogenic sources, and wood combustion were other sources that contributed 23.9%, 23.6%, and 11.5%, respectively. The distribution patterns of PAHs in the YRE and IACZ were influenced by many complicated factors such as sediment grain size, hydrodynamics and so on. Highlights: PAHs are important indicators of anthropogenic activities on the environment. PAHs levels in the Yangtze River Estuary and adjacent coastal areas were studied. Kriging interpolation and PMF model used to study spatial distribution and sources. Anthropogenic activities were the main sources of PAHs in the study area. Distribution patterns influenced by factors like sediment size and hydrodynamics.